House Dust Algae from Aurangabad City of Maharashtra - Jadhav, M J; Jawale, S V (Plantae Scientia, 2021)
House dust contains different biocomponents. Algae are one of the important biocomponents of house dust and is present in the form of spores and filaments. Dust samples were collected from houses of patients suffering from respiratory allergy in Aurangabad city during September 2017 to August 2018. Total of 34 samples were collected and cultured in the petriplates containing agarized Bold’s basal medium (BBM). Algal forms belonged to Chlorophyceae, Bacillariophyceae and Cyanophyceae were cultured and identified. Cyanophycean algae dominated the algal flora of house dust. Algal taxa which were found abundant in-house dust are Chlorococcum humicola, Chlorella vulgaris, Nitzshia palea, Aphanothece nidulans, Phormidium molle, Microcoleus acutissimus, and Plectonema gracillimum. 16 algal taxa recorded in the present study are allergenic to human beings.